Trellises, planters & raised beds for beginners : 30+ easy, unique, and useful projects you can make with common tools and materials (New Shoe Press, 2025)
"In this book, you'll find the perfect partner for constructing useful and attractive trellises, raised beds, planter boxes, window boxes, and more. With easy-to-follow, illustrated build plans requiring only basic tools, you'll be able to make your own outdoor garden projects any time inspiration strikes"--